The analysis of mortality rates in patients with acute ischemic stroke in a hospital at differentiated infusion therapy - Semenenko, A. I. (Journal of Education, Health and Sport, 2016)
Semenenko A. I. The analysis of mortality rates in patients with acute ischemic stroke in a hospital at differentiated infusion therapy. Journal of Education, Health and Sport. 2016;6(6):300-307. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55592 http://ojs.ukw.edu.pl/index.php/johs/article/view/3580 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016. THE ANALYSIS OF MORTALITY RATES IN PATIENTS WITH ACUTE ISCHEMIC STROKE IN A HOSPITAL AT DIFFERENTIATED INFUSION THERAPY A. I. Semenenko Vinnitsa National Medical University M.I. Pirogov Abstract Acute cerebrovascular accident (CVA) is a major cause of morbidity and mortality of the adult population in the world and is in fourth place in the structure of mortality after cancer, cardiovascular diseases and respiratory diseases. Today conducted an intensive search for new materials or new schemes of use existing drugs that could improve current already known treatment of CVA or become the basis for a new more effective and safe drug. The purpose of the work. Conduct analysis of hospital mortality of patients with ischemic CVA on a background of differentiated infusion therapy with various infusion solutions. Materials and methods. As test solutions been used izoosmolar 0.9% solution of NaCl, colloidal izoosmolar solution of Voluven, colloidal hyperosmolar solution of Hekoton, hyperosmolar solution mannitol in groups of patients. Investigated solutions were administered intravenously in conditionally effective dose of 2.5 ml/kg 2 times per day (5 ml/kg per day) (determined experimentally) and then every day every 12 hours for 7 days immediately upon confirmation of the diagnosis using spiral computed tomography (SCT). For the control group were taken patients treated only with infusion solution of 0.9% NaCI, the comparison group were patients received 0.9% NaCI solution+Voluven or Hekoton or Mannitol. The main selection criterion of patients was the presence of CVA by the ischemic type and minds lower of 12-13 score by the Glasgow Coma Scale. Results and discussion. Analyzing the overall structure of mortality should be noted that in the first two days of treatment were not observed deaths in either group of patients with CVA by ischemic type in hospital. At the end of observation overall mortality rate of patients for each study group was: 0,9% NaCl - 8 (32%), Voluven - 6 (24%), hekoton - 3 (12%), mannitol - 8 (32%). Carrying out the statistical analysis of intergroup mortality rate should be noted that only a group of Hekoton which showed the lowest mortality has the significant difference (p = 0.09) compared with groups of 0,9% NaCl and mannitol. Comparing the group of Voluven and Hekoton can talk about different mortality which amounted to 6 (24.0%) and 3 (12.0%) at the end of observation but significant differences between them were not (p = 0.27). Daily analysis of the dynamics of growth of stationary mortality shows the comparability of this indicator in the group of 0,9% NaCl and Mannitol and was from the fifth day 8% vs. 32% (p = 0.03). A group of Voluven showed slightly better results so the growth of mortality was 0% vs. 24% (p = 0.009) from the 3rd day. Only the growth rate of stationary mortality was not statistically significant value and accounted for (p> 0.06) in a group of hekoton. Conclusions 1. The total mortality rate of patients scheduled for each of the group: 0,9% NaCl - 8 (32%), Voluven - 6 (24%), Hekoton - 3 (12%), Mannitol - 8 (32%). 2. Analysis of the mortality rate showed that only group of Hekoton had the least reliable mortality (p = 0.09) compared with groups of 0,9% NaCl and Mannitol in patients with acute ischemic stroke in the hospital with differentiated infusion therapy. 3. Comparison of the groups of Voluven and Hekoton showed no significant difference (p = 0.27) and growth rate of stationary mortality was not statistically significant value and accounted for (p> 0.06) only in the group of Hekoton. Keywords: cerebrovascular accident, ischemic stroke, infusion therapy.